2009
DOI: 10.1002/jcp.21917
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast differentiation is functionally associated with decreased AMP kinase activity

Abstract: Osteoblasts, originating from mesenchymal stem cells, play a pivotal role in bone formation and mineralization. Several transcription factors including runt-related transcription factor 2 (Runx2) have been reported to be essential for osteoblast differentiation, whereas the cytoplasmic signal transduction pathways controlling the differentiation process have not been fully elucidated. AMP-activated protein kinase (AMPK) is a serine-threonine kinase generally regarded as a key regulator of cellular energy homeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 44 publications
10
75
2
1
Order By: Relevance
“…When primary osteoblasts were co-treated with AICAR and compound C, compound C suppressed the stimulatory effect of AICAR on bone nodule formation, supporting a role for AMPK activation in bone formation. However, these results are in contrast to the study showing that osteoblast differentiation is functionally associated with decreased AMPK activity, measured by phosphorylation levels of AMPKa subunit (Kasai et al 2009). We found a similar decrease in baseline AMPK activity with time during osteoblast differentiation.…”
Section: Effect Of Ampk Activation On Bone Cell Activities In Vitro Acontrasting
confidence: 99%
See 2 more Smart Citations
“…When primary osteoblasts were co-treated with AICAR and compound C, compound C suppressed the stimulatory effect of AICAR on bone nodule formation, supporting a role for AMPK activation in bone formation. However, these results are in contrast to the study showing that osteoblast differentiation is functionally associated with decreased AMPK activity, measured by phosphorylation levels of AMPKa subunit (Kasai et al 2009). We found a similar decrease in baseline AMPK activity with time during osteoblast differentiation.…”
Section: Effect Of Ampk Activation On Bone Cell Activities In Vitro Acontrasting
confidence: 99%
“…It causes a large and sustained increase in both AMPKa phosphorylation at Thr-172 and AMPK activation measured by an in vitro peptide phosphorylation assay. Results on osteoblastic MC3T3-E1 cell line are however divergent as AICAR was reported to either phosphorylate AMPK in those cells (Kanazawa et al 2007) or to fail to induce sustained phosphorylation of AMPKa (Kasai et al 2009). Another AMPK agonist, metformin, has uniformly been shown to be a potent stimulator of AMPK activation in bone marrow progenitor cells (BMPC; Molinuevo et al 2010), primary osteoblasts (Shah et al 2010), MC3T3-E1 cells , Kasai et al 2009), ROS 17/2.8 cells (Shah et al 2010), and primary bone marrow macrophages .…”
Section: Subunit Expression and Ampk Regulation In Bone Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there has been contradictory evidence among published results regarding AMPK regulation of osteoblast differentiation. A study in primary osteoblasts and MC3T3-E1 osteoblastic cells found that phosphorylation of AMPK is significantly decreased during osteoblastic differentiation and that matrix mineralization is significantly inhibited by activated AMPK (13). Two other independent studies showed that metformin administration enhances osteogenic differentiation of bone marrow progenitor cells and stimulates bone lesion regeneration, whereas aminoimidazole carboxamide ribonucleotide (AICAR) treatment causes significant bone loss (14,15).…”
Section: Ampkmentioning
confidence: 99%
“…Cortizo et al (2006) also found that metformin had no effect on ALP activity in UMR106 rat osteosarcoma cells. At the concentration of 2 mM, metformin reduced mineralization of osteoblasts (Kasai et al 2009). These conflicting results may be attributed to the different culture conditions and cell sources.…”
Section: Discussionmentioning
confidence: 98%